Legal law and principles in the credit in banking - Mega Mustika (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
In lending from banks to the public for financing purposes, each bank is required to implement the principle of prudence. The formulation of the problem in the research is how to apply the law and the principle of prudence in anticipating the occurrence of bad credit. This study aims to find conformity in the law and the practice of applying the precautionary principle. This research is normative research, using the statutory approach. In this study using legal materials to conduct analysis in the form of primary legal materials, tertiary legal materials or non-legal legal materials and analyzed using descriptive methods. The results of the study indicate that the application of the prudential banking principle in granting credit can be interpreted as the principle applied by the bank in carrying out its business, so that it is always in accordance with applicable banking provisions, in order to avoid irregularities in unhealthy banking practices and to minimize losses incurred on banks such as bad credit.prudential principle; bad credit; banking